2017
DOI: 10.3390/ijms18061167
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Extracellular Matrix Production by Adipose Tissue-Derived Stem Cells for Development of Wound Healing Therapies

Abstract: The synthesis and deposition of extracellular matrix (ECM) plays an important role in the healing of acute and chronic wounds. Consequently, the use of ECM as treatment for chronic wounds has been of special interest—both in terms of inducing ECM production by resident cells and applying ex vivo produced ECM. For these purposes, using adipose tissue-derived stem cells (ASCs) could be of use. ASCs are recognized to promote wound healing of otherwise chronic wounds, possibly through the reduction of inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 84 publications
0
36
0
2
Order By: Relevance
“…In injured sites, ADSCs were recruited and were migrated by increasing their expression of CXCR-4 molecules, which led to modulating the inflammatory phenotype of local immune cells to a healing anti-inflammatory one. Their presence was critical to drive the inflammatory profile of macrophages, T, B, and dendritic cells initiating, and thus the proliferation and remodeling phases of wound healing [51,52]. Their action was likely activated by TGF-β or GDF11 or both of them [53].…”
Section: Role Of the Microenvironment In Adscs Inductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In injured sites, ADSCs were recruited and were migrated by increasing their expression of CXCR-4 molecules, which led to modulating the inflammatory phenotype of local immune cells to a healing anti-inflammatory one. Their presence was critical to drive the inflammatory profile of macrophages, T, B, and dendritic cells initiating, and thus the proliferation and remodeling phases of wound healing [51,52]. Their action was likely activated by TGF-β or GDF11 or both of them [53].…”
Section: Role Of the Microenvironment In Adscs Inductionmentioning
confidence: 99%
“…Allogenic fibroblasts were first used to support skin architecture by providing ECM protein secretion, but also by feeding surrounding skin cells by growth factors involved in cell proliferation and tissue regeneration. Using ADSCs within these skin substitutes have permitted the rapid reconstitution, more micro-vasculatures, more elasticity and better dermal cell compositions with high ECM secretion resulting in proliferation, and the remodeling phases of wound healing [52]. Skin has a more satisfying esthetic appearance and function, consequently overcoming the CEA limitations observed, such as recurrent open wounds and fragility, and the extensive ECM protein production leading to scar contractions [91].…”
Section: Adscs Issues Between Hopes and Limitsmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, delayed wound healing not only leads to increasing healthcare costs but also seriously impairs the quality of life in DM patients. Because the traditional therapies are often insufficient, a novel method to promote diabetic wound healing is of considerable interest at present (Hyldig et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that CB hematopoietic progenitors influence the expression of genes encoding for adhesion molecules and molecules of the connective tissue matrix [143]. Its remodeling enzymes was also studied in multipotent mesenchymal stromal cells (MSCs) from human adipose tissue [144]. In a direct cell-cell contact culture system, WJ-MSCs enhanced the expansion of CB-CD34+ cells [145].…”
Section: Past and Future Perspectivesmentioning
confidence: 99%